Efficient Ion Sieving in Covalent Organic Framework Membranes with Sub‐2‐Nanometer Channels. Issue 44 (4th September 2021) - Sheng, Fangmeng; Wu, Bin; Li, Xingya; Xu, Tingting; Shehzad, Muhammad A.; Wang, Xiuxia; Ge, Liang; Wang, Huanting; Xu, Tongwen
Abstract: Membranes of sub‐2‐nanometer channels show high ion transport rates, but it remains a great challenge to design such membranes with desirable ion selectivities for ion separation applications. Here, covalent organic framework (COF) membranes with a channel size of ≈1.4 nm and abundant hydrogen bonding sites, exhibiting efficient ion sieving properties are demonstrated. The COF membranes have high monovalent cation permeation rates of 0.1–0.2 mol m −2 h −1 and extremely low multivalent cation permeabilities, leading to high monovalent over divalent ion selectivities for K + /Mg 2+ of ≈765, Na + /Mg 2+ of ≈680, and Li + /Mg 2+ of ≈217. Experimental measurements and theoretical simulations reveal that the hydrogen bonding interaction between hydrated cations and the COF channel wall governs the high selectivity, and divalent cations transport through the channel needs to overcome higher energy barriers than monovalent cations. These findings provide an effective strategy for developing sub‐2‐nanometer sized membranes with specific interaction sites for high‐efficiency ionic separation. Abstract : Ultrathin covalent organic framework membranes are constructed, where abundant hydrogen bonding sites are lined in the 1D sub‐2‐nm sized channels. The hydrogen‐bond binding interaction between the hydrogen bonding sites and hydrated divalent cations are stronger than that of monovalent cations, enabling efficient metal ion sieving driven by the concentration gradient.